Role of adenosine in oligodendrocyte precursor maturation - Coppi, Elisabetta; Cellai, Lucrezia; Maraula, Giovanna; Dettori, Ilaria; Melani, Alessia; Pugliese, Anna Maria; Pedata, Felicita (Frontiers in Cellular Neuroscience, 2015)
Differentiation and maturation of oligodendroglial cells are postnatal processes involving specific morphological changes correlated with the expression of stage-specific surface antigens and functional voltage-gated ion channels. A small fraction of oligodendrocyte progenitor cells (OPCs) generated during development are maintained in an immature and slowly proliferative or quiescent state in the adult central nervous system (CNS) representing an endogenous reservoir of immature cells. Adenosine receptors are expressed by OPCs and a key role of adenosine in oligodendrocyte maturation has been recently recognised. As evaluated on OPC cultures, adenosine by stimulating A1 receptors, promotes oligodendrocyte maturation and inhibits their proliferation; on the contrary by stimulating A2A receptors, it inhibits oligodendrocyte maturation. A1 and A2A receptor-mediated effects are related to opposite modifications of outward delayed rectifying membrane K+ currents (IK) that are involved in regulation of oligodendrocyte differentiation. Brain A1 and A2A receptors might represent new molecular targets for drugs useful in demyelinating pathologies, such as multiple sclerosis (MS), stroke and brain trauma.